Interdisciplinary pain program participants with high catastrophizing scores improve function utilizing enriched therapeutic encounters and integrative health techniques: a retrospective study - Vora, Ariana; Kennedy-Spaien, Eve; Gray, Sarah; Estudillo-Guerra, Anayali Maria; Phillips, Gabriele; Mesia-Toledo, Ines; Glenn, Mel; Chin, Bridget S.; Morales-Quezada, Leon (Frontiers in Psychology, 2024)
Introduction Pain catastrophizing describes helplessness, rumination, and magnification of a pain experience. High pain catastrophizing is an independent risk factor for disability, pain severity, inadequate treatment response, chronicity, and opioid misuse. Interdisciplinary pain programs (IPPs) are beneficial and cost-effective for individuals with chronic pain, but their functional impact on individuals with high pain catastrophizing is not well established. The emerging field of placebo studies suggests that patient-provider relationships, positive treatment expectations, and sociobiologically informed care trigger physiological responses that may enhance therapeutic interventions. Methods In this retrospective observational cohort study, we compared admission and discharge data for 428 adults with high-impact chronic pain (mean 8.5 years) who completed the Spaulding-Medford Functional Restoration Program (FRP). The interdisciplinary FRP team of physiatrists, behavioral health clinicians, physical therapists, and occupational therapists specializes in evidenced-based conventional rehabilitation, integrative health, and pain psychoeducation via enriched therapeutic encounters, fostering collaboration, validation, trust, self-efficacy, and positive expectations. Clinical outcome measures included the Canadian Occupational Performance Measure (COPM) assessing functional performance (COPM-PS) and satisfaction with function (COPM-SS), the Pain Numeric Rating Scale (NRS), the Pain Catastrophizing Scale (PCS), and the Patient Health Questionnaire-9 (PHQ-9). Results FRP participants with clinically elevated catastrophizing at baseline (PCS ≥30, mean PCS 39) achieved statistically significant improvements in function (mean delta -2.09, CHI2 = 15.56, p < 0.001), satisfaction with function (COPM-SS mean delta -2.50, CHI2 = 7.42, p = 0.007), pain (NRS mean delta 2.7), mood (PHQ-9 mean delta 1.87, p = 0.002), and catastrophizing (PCS mean delta 4.16, p < 0.001). Subgroup analysis revealed racial disparities in pain scores, and exploratory analysis showed a trend toward reducing opiate consumption. Discussion Despite the known association of adverse outcomes with high catastrophizing, FRP participation was associated with increased productive engagement, reduced pain, reduced maladaptive thought processes, and improved mood. Although causation and efficacy cannot be established from a retrospective design, this is the first study to identify functional improvement in patients with high-impact chronic pain and clinically relevant high pain catastrophizing who participate in an IPP combining conventional and complementary rehabilitation with psychoeducation. These enriched therapeutic encounters may enhance the treatment process by promoting trust, empathy, collaboration, and beneficial reframing of patients’ experiences, expectations, and goals.